2018
DOI: 10.5194/acp-18-31-2018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of short-term effective radiative forcing of fire aerosols over North America using nudged hindcast ensembles

Abstract: Abstract. Aerosols from fire emissions can potentially have large impact on clouds and radiation. However, fire aerosol sources are often intermittent, and their effect on weather and climate is difficult to quantify. Here we investigated the short-term effective radiative forcing of fire aerosols using the global aerosol-climate model Community Atmosphere Model version 5 (CAM5). Different from previous studies, we used nudged hindcast ensembles to quantify the forcing uncertainty due to the chaotic response t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…of large-scale clouds are parameterized using the prognostic cloud fraction and prognostic condensate (PC2) scheme (Wilson et al, 2008a, b) with modifications described in Morcrette (2012). The atmospheric boundary layer is parameterized using the turbulence closure scheme of Lock et al (2000) with modifications described in Lock (2001) and Brown et al (2008).…”
Section: Model Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…of large-scale clouds are parameterized using the prognostic cloud fraction and prognostic condensate (PC2) scheme (Wilson et al, 2008a, b) with modifications described in Morcrette (2012). The atmospheric boundary layer is parameterized using the turbulence closure scheme of Lock et al (2000) with modifications described in Lock (2001) and Brown et al (2008).…”
Section: Model Detailsmentioning
confidence: 99%
“…In order to avoid issues regarding the representativeness of a limited number of years of meteorology, it would be useful to do future work such as that performed here using multiple years of data. Noise in some of the fields shown here may also be reduced by employing an ensemble approach as in Liu et al (2018).…”
Section: Recommendationsmentioning
confidence: 99%
“…This allows for a direct, time evolving calculation of ERF based on differences in top-of-atmosphere radiative imbalance between the simulations (Chen and Gettelman, 2016;Liu et al, 2018). Although they may not capture the full range of atmospheric adjustments (Forster et al, 2016), nudged ERF calculations are sufficiently comparable to fSST based calculations that they will be used in CovidMIP provided they have prescribed the same emissions as described above.…”
Section: Erf Calculationsmentioning
confidence: 99%
“…Fire imposes great impacts on global climate through effects on radiative forcing, terrestrial ecosystems, and biogeochemical cycling (Li and Lawrence 2017). The feedback mechanisms between fire and climate interactions are still a great challenge and remain fundamentally uncertain (Liu et al 2014;Hantson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With a regional model, Lu and Sokolik (2013) found that fire aerosols lead to an increase of cloud water path during Canadian boreal wildfires in the summer of 2007. Liu et al (2018) found that fire aerosols have significant impacts on both liquid and ice clouds over southern Mexico and the central United States during the fire events in April 2009.…”
Section: Introductionmentioning
confidence: 99%